濾胞性リンパ腫を治療するための併用療法におけるＣＤ３及びＣＤ２０に対する二重特異性抗体 (2023)
リツキシマブ及びベンダムスチンの標準治療レジメンと組み合わせて、ＣＤ３及びＣＤ２０に結合する二重特異性抗体を使用する、ヒト対象における濾胞性リンパ腫（例えば、再燃性及び／又は難治性濾胞性リンパ腫）の臨床治療方法が提供される。【選択図】図2 Provided are methods of clinical treatment of follicular lymphoma (for example, relapsed and/or refractory follicular lymphoma) in human subjects using a bispecific antibody which binds to CD3 and CD20 in combination with standard of care regimens of rituximab and bendamustine.